Določitev kalcijevih kromatov Ca5(CrO4)3O0,5, Ca3(CrO4)2 in Ca5(CrO4)3 z rentgensko difrakcijo, optičnim in elektronskim mikroskopom - Dobnikar, Meta (Kovine zlitine tehnologije, 1995)
Calcium chromates Ca5(CrO4)3O0,5, Ca3(CrO4)2 and Ca5(CrO4)3, that form in the reaction of CaO with Cr2O3 at different temperatures have been synthetized. Mineral phases formed have been identified by means of x-ray powder diffraction. Phases were investigatead with optical microscope. In reflected polarized light Ca3(CrO4)2 is brighter than Ca5(CrO4)3O0,5 ans Ca5(CrO4)3 and it is also more resistant to HCl. In thin sections mineral phases do not differ significantly, but the influence of firing temperature on crystal size is obvious. Scanning electron microscopy showed that mineral phases differ by morphology.
Keywords: sinteza; kalcijevi kromati; kemijska kinetika; kemijske reakcije